Electrochemical Characterization and DNA Interaction Studies of a Novel Copper Schiff Base Complex: Insights From Cyclic Voltammetry and Molecular Docking - ZOUBEIDI, Chahinaz; OURARI, Ali; LANEZ, Elhafnaoui; LANEZ, Touhami (Studia Universitatis Babeș-Bolyai Chemia, 2024)
In this study, we investigate the electrochemical properties of a novel copper complex (CuL2) derived from the Schiff base ligand N-3-bromopropylsalicylaldimine (LH). We also examine its interaction with chicken blood double-stranded DNA (cb-ds DNA) in phosphate buffer solution (PB) at physiological pH 7.2 using cyclic voltammetry (CV) techniques. The interaction mechanism of nitrite with CuL2, involving the CuII/CuI redox system, is explored. The CuL2 complex was electropolymerized on glassy carbon (GC) and fluorine tin oxide (FTO). The morphology of PolyCuL2 formed on FTO was analyzed using scanning electron microscopy (SEM) and its elemental composition determined by EDX analysis. The modified electrode polyCuL2/GC exhibited efficient catalytic activity for the electroreduction of oxygen (O2) in homogeneous electrocatalytic media. The binding constant (Kb) of the DNA-CuL2 adduct, determined from CV measurements, was found to be 1.33×105, closely matching the value obtained from molecular docking studies (1.75×105). Docking studies indicate that the CuL2 complex binds to DNA in the minor groove binding mode. The anodic peak potential shift in the negative direction suggests an electrostatic interaction between CuL2 and DNA.